SARS-CoV-2 Threat Perception and Willingness to Vaccinate: The Mediating Role of Conspiracy Beliefs - Maftei, Alexandra; Holman, Andrei Corneliu (Frontiers in Psychology, 2021)
In the current exploratory study, we investigated the willingness of participants to vaccinate against the novel coronavirus [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] that has shaken up the world since the beginning of 2020. More specifically, we tested the mediating role of conspiracy beliefs (CBs) on the relationship between threat perception (TP) and willingness of participants to vaccinate against coronavirus disease 2019 (COVID-19), along with a series of associated demographic variables. Overall, 40% of our sample expressed total rejection of the COVID-19 vaccine. Our results suggested no significant differences in gender, age, educational level, and vaccine acceptance or hesitancy of participants. The results also indicated that CBs partially mediated the relationship between TP and willingness of participants to vaccinate. The current findings are discussed within the theory of planned behavior (TPB) framework and their importance for public health communication and practices and building public trust within the global fight against COVID-19. We considered the present results as a valuable starting point in understanding the psychological constructs related to the extended model of TPB and other personal factors and addressed the attitudinal roots that shape the acceptance and rejection of COVID-19 vaccination.